Chemical-grafting of graphene oxide quantum dots (GOQDs) onto ceramic microfiltration membranes for enhanced water permeability and anti-organic fouling potential - Gu Q. (Elsevier B.V., 2020)
10.1016/j.apsusc.2019.144128